Analisis Faktor Risiko Preeklamsi pada Ibu Bersalin: Studi Cross-Sectional di Pelayanan Kesehatan - Wilis Dwi Pangesti; Dwi Astuti; Evicenna Naftuchah Riani (Jurnal Skala Kesehatan, 2026)
Preeclampsia is a serious condition that contributes to increased maternal and infant morbidity and mortality, impacting living and medical care costs. This study aims to analyze the factors associated with preeclampsia, focusing on age, history of hypertension, personal and family history of preeclampsia, pre-pregnancy obesity, and MAP over 90 mmHg. Using a correlational analytic method and Cross sectional study design, this research involved 102 randomly selected postpartum women from a population of 2109 samples. Data were analyzed using Spearman's rho and Contingency Coefficient Correlation tests via SPSS version 2.9. Results indicated that age under 20 and over 35, history of hypertension, personal and family history of preeclampsia, pre-pregnancy obesity, and MAP over 90 mmHg were significantly associated with preeclampsia, with all p-values <0.001 and r-values ranging from 0.315 to 0.390. The findings highlight the importance of early detection of these risk factors from preconception and pregnancy stages to prevent preeclampsia. This study recommends enhancing screening efforts and health education for women of childbearing age to reduce the risk of preeclampsia.